MIOPATI KONGENITAL PADA BAYI: SEBUAH LAPORAN KASUS - Rangga Adinugraha (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Background: The congenital myopathies are group of genetic muscle disorders with a prevalence estimated between 1:22,480 in Sweden and 1:135,000 in Northern England. The most severe forms of congenital myopathy present In infant is the floppy infant with hypotonia and generalized musle weakness, and a frog leg posture, with facial, bulbar and respiratory weakness. We will provide an approach to the diagnosis of congenital myopathies with clinical examination, muscle imaging (MRI), muscle biopsy and identifying the genetic basis. Management of congenital myopathy are treatment of symptoms and complication caused by myopathies. Aim: To report a case of congenital myopathy in infant Case Description: A boy, a month, consulted from pediatric department to neurology department with chief complains the mouth is held in a open position, difficulty in feeding and generalized muscle weakness. From physical examintaion shows hypotonus in the masseter muscle, bulbar, respiration and all of extremities. In the chest cavity show pectus excavatum. Reflexes decrease in all of extremities with phatological reflexes in both lower extremities. We found pneumonia bilateral from thorax X-ray. ENMG shows moderate to severe axonal neuropathy and demyelination on all of extremities with normal EMG results. He received paracetamol 30 mg iv, ampicilin 150 mg iv, gentamicin 12 mg iv. He received exercise and chest fisiotherapy. After 22 days of treatment, he was discharge with clinical improvement. Conclusion: Patient has pneumonia bilateral caused by respiratory weakness congenital myopathy. Follow up and histological features is essential in guiding management for prediction of prognosis.